Reflections on Targeted Poverty Programs in Latin America - Levy, Santiago (2009)
Santiago Levy MARTIN J. FORMAN MEMORIAL LECTURE Controversial Issues on the Role of Conditional Cash Transfer Programs to Improve Nutrition 19th Annual Martin J. Forman Memorial Lecture APR 17, 2009 - 03:30 PM TO 04:30 PM UTC